Impact of environmental programs on student test scores mediated by school attendance rate - Bo Ye; Recai Yucel; Yanji Qu; George Thurston; Xinlei Deng; Ian Ryan; Shao Lin (Elsevier, 2022)
Background: Little is known regarding whether environmental programs affect student academic performance. We examined if the association between EPA Tools for School (TfS) policies or other environmental programs and student test scores were mediated by student attendance. Methods: The 2015 School Building Condition Survey (BCS) was linked with School Report data provided by the New York State Education Department (NYSED). BCS includes school building information from 2,956 public schools while School Report data provides school attendance and test scores for different subjects in NYS. We conducted causal mediation analysis to investigate direct and indirect effects of TfS or other programs, via improving attendance, on test scores for each course while controlling for school-level socio-demographics. Results: EPA TfS policies were significantly associated with a lower percent of "low total score" for overall math, overall science, and multiple specific subjects (all P < 0.05). Furthermore, the associations between TfS and test scores in algebra II, trigonometry, and chemistry were significantly mediated by student attendance rate (-1.376 and -0.563 respectively). Other IAQ programs were also associated with a smaller percent of low-score students in multiple subject tests (all P <0.05). We found a mediated proportion of 6 to 43% by attendance in the association between other IAQ programs and high score academic performance. Implementing TfS and other programs can reduce the proportion of students receiving overall low scores by 2.66% and 1.37%, respectively. Conclusion: EPA TfS and other IAQ programs improved student test scores in multiple subjects in NYS public schools and was partially mediated by improving attendance rate.